2020
DOI: 10.1007/s12325-020-01550-4
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Favors Thrombus Recanalization and Survival in Patients With Liver Cirrhosis and Portal Vein Thrombosis: Results of a Meta-Analysis

Abstract: Introduction: Benefit and risk of anticoagulation in cirrhotic patients with portal vein thrombosis (PVT) remain controversial, especially in those with asymptomatic PVT and in non-liver transplant candidates. Furthermore, the predictors of portal vein recanalization and bleeding events after anticoagulation are critical for making clinical decisions, but still unclear. We conducted a meta-analysis to investigate the outcomes of anticoagulation for PVT in liver cirrhosis and explore the predictors of portal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 60 publications
(119 reference statements)
2
66
1
Order By: Relevance
“…Indeed, if the benefit-to-risk ratio of anticoagulation therapy in other contexts, such as atrial fibrillation, was evaluated in trials that included several thousand patients, the results differed [26][27][28][29][30][31][32][33][34][35]. Similar results and limitations were recently reported in a systematic review with a meta-analysis from China [24]. The above data cast doubt on the negative role of PVT in the natural history of cirrhosis.…”
Section: Efficacy and Risks Of Treatment For Pvt In Cirrhosismentioning
confidence: 61%
See 2 more Smart Citations
“…Indeed, if the benefit-to-risk ratio of anticoagulation therapy in other contexts, such as atrial fibrillation, was evaluated in trials that included several thousand patients, the results differed [26][27][28][29][30][31][32][33][34][35]. Similar results and limitations were recently reported in a systematic review with a meta-analysis from China [24]. The above data cast doubt on the negative role of PVT in the natural history of cirrhosis.…”
Section: Efficacy and Risks Of Treatment For Pvt In Cirrhosismentioning
confidence: 61%
“…Recently, a meta-analysis of 33 studies, which included 1696 cirrhotics, reported that anticoagulation (AC) therapy significantly improved overall survival without influencing overall bleeding [24]. However, the surveyed studies included heterogeneous populations and were predominantly retrospective; some were presented only in an abstract form, and none were randomized or controlled.…”
Section: Does Pvt Worsen the Outcome Of Cirrhosis?mentioning
confidence: 99%
See 1 more Smart Citation
“…54 A recent meta-analysis of 33 studies (n=1,696 patients with cirrhotic PVT who received conventional anticoagulants) reported that decompensated cirrhosis may be associated with lower PV recanalization rates in patients who are administered anticoagulants. 55 Early anticoagulation initiation (risk ratio [RR] 1.58, 95% CI 1.21-2.07, P<0.001) significantly increased PV recanalization. Furthermore, decompensated cirrhosis (RR 0.77, 95% CI 0.62-0.95, P=0.02) and higher MELD scores (mean difference -1.48, 95% CI -2.20-0.76, P<0.001) were significantly associated with low PV recanalization rates.…”
Section: Efficacy and Safety Of Low-molecular-weight Heparin And Vitamin K Antagonist Treatmentsmentioning
confidence: 99%
“…Furthermore, decompensated cirrhosis (RR 0.77, 95% CI 0.62-0.95, P=0.02) and higher MELD scores (mean difference -1.48, 95% CI -2.20-0.76, P<0.001) were significantly associated with low PV recanalization rates. 55 Bleeding, one of the most common complications of anticoagulation therapy, occurred in 5% of patients with cirrhosis and PVT who received anticoagulants. 54 A meta-analysis of six studies that included 257 patients with cirrhosis and PVT reported no difference in total bleeding rates between the anticoagulation and no-anticoagulation groups (11% in both groups).…”
Section: Efficacy and Safety Of Low-molecular-weight Heparin And Vitamin K Antagonist Treatmentsmentioning
confidence: 99%